Threshold effect of working capital management on firm profitability: evidence from Vietnam - Nguyen Thanh Hung; Thanh Su Dinh (Cogent Business & Management, 2022)
The purpose of this paper is to investigate the non-linear relationship between working capital management (WCM) and firm profitability (FP). As well as checking whether there is a financial leverage threshold in the decision on working capital, thereby assessing the change in the impact of working capital on corporate profits with a defined threshold. Through panel data of 405 enterprises listed on the Vietnam stock exchange in the period from 2010 to 2020, compiled by Thomson Reuters (2021), The study uses Hansen's (1999) threshold estimate (fixed-effects panel threshold model) to determine the threshold and estimate the model's parameters. Research results have been found: (i) there exists a non-linear relationship be tween working capital management and corporate profitability; and (ii) at a certain percentage of the debt coefficient (Impact Threshold), the variables representing working capital management all have a negative impact on the profitability of the firm. In this relationship, there are different effects of the proxies of Working Capital Management before and after the threshold, and specifically, the impact values of these proxies are higher after the threshold. This implies that tighter working capital management depends on the profitability of the business. This is the first study to clarify the effect of working capital in terms of the capital structure of enterprises. At a certain leverage threshold, the business will decide to optimize the appropriate working capital management to improve profitability.
Keywords: M10; G32; G30; G31; L60; 650; profitability; emerging economy; threshold; working capital management